Cryogenic flow rate measurement with a laser Doppler velocimetry standard. (15th February 2018) - Maury, R; Strzelecki, A; Auclercq, C; Lehot, Y; Loubat, S; Chevalier, J; Ben Rayana, F; Olsen, Å A F; Chupin, G
Abstract: A very promising alternative to the state-of-the-art static volume measurements for liquefied natural gas (LNG) custody transfer processes is the dynamic principle of flow metering. As the Designated Institute (DI) of the LNE ('Laboratoire National de métrologie et d'Essais', being the French National Metrology Institute) for high-pressure gas flow metering, Cesame–Exadebit is involved in various research and development programs. Within the framework of the first (2010–2013) and second (2014–2017) EURAMET Joint Research Project (JRP), named 'Metrological support for LNG custody transfer and transport fuel applications', Cesame–Exadebit explored a novel cryogenic flow metering technology using laser Doppler velocimetry (LDV) as an alternative to ultrasonic and Coriolis flow metering. Cesame–Exadebit is trying to develop this technique as a primary standard for cryogenic flow meters. Currently, cryogenic flow meters are calibrated at ambient temperatures with water. Results are then extrapolated to be in the Reynolds number range of real applications. The LDV standard offers a unique capability to perform online calibration of cryogenic flow meters in real conditions (temperature, pressure, piping and real flow disturbances). The primary reference has been tested on an industrial process in a LNG terminal during truck refuelling. The reference can calibrate Coriolis flow meters being used daily with all the real environmental constraints, and its utilisation is transparent for LNG terminal operators. The standard is traceable to Standard International units and the combined extended uncertainties have been determined and estimated to be lower than 0.6% (an ongoing improvement to reducing the correlation function uncertainty, which has a major impact in the uncertainty estimation).